COMPARATIVE CHARACTERISTICS OF ACTIVITY IN PROFESSIONAL SELF-EDUCATION OF STUDENTS OF I-V COURSES PEDAGOGICAL UNIVERSITY (Pedagogy of Higher and Secondary Education, 2008)
The article describes the development of future teachers' activity in the process of selfeducation from first to last course of the university.
Keywords: 1